2014
DOI: 10.3389/fimmu.2014.00218
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cell Therapy in an Allogeneic-Hematopoietic Cell Transplantation Setting: An Effective Strategy toward Better Disease Control?

Abstract: Hematopoietic cell transplantation (HCT) is a last treatment resort and only potentially curative treatment option for several hematological malignancies resistant to chemotherapy. The induction of profound immune regulation after allogeneic HCT is imperative to prevent graft-versus-host reactions and, at the same time, allow protective immune responses against pathogens and against tumor cells. Dendritic cells (DCs) are highly specialized antigen-presenting cells that are essential in regulating this balance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 90 publications
0
12
0
Order By: Relevance
“…This highlights the need for personalized ATG dosing regimens to maintain effective T cell depletion without inhibiting IR after HCT. It also opens up important avenues for additional immunotherapy to skew specific T cell responses after UCBT against previously identified tumor-associated antigens [107] or infectious agents [108,109]. In all, these findings emphasize the requirement of interpreting the results from comparative studies on IR or clinical effects after HCT with different stem cell sources in light of the absence or presence of T celledepleting serotherapy.…”
Section: Concluding Remarks and Future Perspectivementioning
confidence: 79%
“…This highlights the need for personalized ATG dosing regimens to maintain effective T cell depletion without inhibiting IR after HCT. It also opens up important avenues for additional immunotherapy to skew specific T cell responses after UCBT against previously identified tumor-associated antigens [107] or infectious agents [108,109]. In all, these findings emphasize the requirement of interpreting the results from comparative studies on IR or clinical effects after HCT with different stem cell sources in light of the absence or presence of T celledepleting serotherapy.…”
Section: Concluding Remarks and Future Perspectivementioning
confidence: 79%
“…More notably, few recent DC vaccinations studies after allo-HCT have shown to be safe and efficient regarding both clinical and immunological responses. Hopefully, the field is open for further investigations, especially with the current approaches in achievable combination therapies to lessen the relapse rates and improve the survival rates [80]. To wrap up, these reports point to the feasibility of using DC-based immunotherapy as an immunogenic adjuvant after remission-induction therapy in AML patients, although it necessitates further studies.…”
Section: Phagocytic Functionmentioning
confidence: 99%
“…Dendritic cells (DCs) are highly specialized antigen-presenting cells that regulate the balance between action (relevant for GVL) and suppression of the immune system (relevant for GVHD). 96 Therefore, DC vaccination is of major interest as a tool to modulate immune responses after allo-HCT. For BMT/peripheral blood cell transplantation, DCs can either be obtained by culturing monocytes into monocyte-derived DCs, or by directly isolating plasmacytoid DCs or conventional (myeloid) DCs from the peripheral blood of the donor.…”
Section: Cellular Immunotherapies To Improve Immunitymentioning
confidence: 99%